Evaluasi Pelaksanaan Pengadaan Barang/Jasa Pemerintah dalam Mewujudkan Good Governance (Studi Penelitian di Dinas Cipta Karya dan Tata Ruang Kota Batam) - Hamidi Hamidi (EQUILIBIRIA, 2020)
The objectives of this research is to know how setup law on public procurement on goods/services, how the implementation of public procurement o and what are the barriers factors and alternative solutions in public procurement. The writing methods are normative and empirical methods. The result of this study are shown that Presidential Decree Number 16 Years 2018 as the legal arrangements for public procurement can be used as complete guidelines in the public procurement on goods/services; the implementation of the legal arrangements are not optimal yet; there is an overlap of job function and human resources competencies is not comply yet. The recommendation of this study are the implementation of Presidential Decree Number 16 Years 2018 will be effective since there is local regulations/Mayor Decree as a technical guidance to things that are still not regulated, so that the legal arrangements for the public procurement on goods/services can be used as complete guidelines in the public procurement; must develop the level of compliance in implementing or implementing the Presidential Decree and several other technical regulations; make a clear of job description and human resources competencies need to be improved.